Crafting Based Learning : Solusi Cerdas dalam Mengatasi Keterlambatan Kosakata Bahasa Inggris Siswa Kelas 5 SDN 105289 Desa Kolam. - Melisa Dita Aqila; Annisa Najla Rezkiandi Ritonga; Joya Amelia Situmorang; Natasya Amelia Vega Sitorus; Rahmilawati Ritonga (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Vocbulary (Verb) is a fundamental aspect of English language learning from the elementary level. However, young learners often face difficulties in memorizing, spelling, pronouncing, and understanding new vocabulary due to limited cognitive development and traditional teaching methods. This study aims to explore the effectiveness of crafting as a contextual, engaging, and age-appropriate vocabulary teaching approach. Through a literature review method, this research analyzes various academic sources supporting the integration of hands-on craft activities in the learning process. The findings indicate that crafting promotes student engagement through problem-solving, social interaction, and creative expression. This medium has proven to significantly enhance motivation, comprehension, and vocabulary retention. The study recommends crafting as a holistic and experience-based vocabulary learning strategy for elementary school students.